Examining the Impact of Demand-Side Management Through Dynamic Simulation: Integrating Smart-Grid-Ready Control of Residential Heat Pumps - Horváth, Miklós; Takács, Zoltán; Gergely, László Zsolt (Vysoké učení technické v Brně,Fakulta stavební, 2024)
This paper investigates the suitability of air-to-water heat pumps for smart grids, with a particular focus on load shifting. The research uses dynamic building energy simulations to show that the utilisation of these features effectively addresses the energy consumption challenges of heat pumps while ensuring that heating and domestic hot water demands are met. The implemented control system successfully shifts the morning and evening peaks to the daytime period, resulting in a modest 2% increase in total energy demand. These results not only demonstrate the balancing of heat pump energy consumption, but also provide insights for the development of objective functions. Such functions can play a key role in supporting the smooth integration of renewables into the wider energy framework.
Keywords: Smart Grid; heat pump; demand-side management; dynamic simulation